Evaluation of aftercare program in ALAmal complex by using CIPP model - Hajari Ahmed, Alayshi; Fauziah Ibrahim, Aizan Sofia Amin, Mohammad Rahim, (Opción, 2019)
Kingdom of Saudi Arabia has confronted drugs addiction by developing numerous programs such as the “Aftercare Program”. But there is the problem of relapse. This led the researcher to evaluate the aftercare program in AlAmal Complexes by using CIPP Model from the perspective of the social workers and drug abusers. The objective was to identify the level of (Context, Input, Process and Product) as the main elements of the aftercare program. The results showed that the majority of those have an agreement of the effective level of the context, input, process and product to contribute to the treatment of addiction.